OFFLAND: NARRATIVES, IMMERSION AND INTERACTION IN VIRTUAL REALITY - Silva, Rafael Azevedo (2020)
The project consists in the building of a fiction world and creation of a virtual reality (VR) experience, exploring the potential of this medium for immersion and storytelling. An original fiction world was used: Offland, which is a fantasy approach to the western genre, centered around an inhospitable wasteland. We worked lightly in the world building of maps, regions, civilizations, races and cultures. The project is based on McDowell’s methodology (2019), in which the design of a world precedes the telling of a story. The VR experience portrays one specific scenario of an illusion inducing oasis, centering the experience in exploration, survival and altered states of mind such as hallucinations. The Virtual Environment serves us as a sandbox to test different moments and experiences, to answer in what ways fiction storytelling can be enhanced by virtual reality’s interactivity. We interpreted Brett Leonard’s concept of Storyworlding (as quoted in Bailenson, 2016) through short narratives distributed through space, in which the user participates naturally through interaction with the environment. The virtual experience also explores user participation, allowing for users to leave voice recordings for the next users, and creating a more collective narrative. Through user testing we found that the experience should start with a goal to guide exploration, balancing linearity and nonlinearity allows for a narrative that’s both comprehensive and engaging, the lack of characters or their representation causes little emotion and empathy, details make the fictional world more discernible, and participation should not be forced, it should feel simple to the user. In the literature review that served as basis for the development of the project we present different approaches to storytelling that make use of the potential of VR, principally through space and nonlinearity. A relation is created between the physical reality, the user, virtual reality and different types of immersion. Immersion is separated into sensorial immersion, mental or imaginary immersion, challenge-based immersion and emotional immersion for better understanding. The concept of diegetic user interfaces, controls and interactive objects is also explored with the focus being on narratives. We believe that this project presents useful conclusions for practical fiction worldbuilding and translating it into VR production and storytelling.